PERTANGGUNGJAWABAN BAGI NOTARIS YANG MENOLAK PROTOKOL NOTARIS DI KABUPATEN SLEMAN - Pramesta, Zalfa Ayu (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
This research aims to analyze the liability of notaries who reject protokols from other notaries. To achieve the objectives of this research, a normative juridical research method was used. The data analysis used is qualitative data analysis. The results of the research and discussion concluded that rejecting a notary's protokol is not justified, because every notary is obliged to accept a notary's protokol from another notary, this is stated in the notary's appointment letter. The notary who holds the notary protokol only has the responsibility to secure state documents, submit minutes of the deed if needed, if there is a problem with the notarial protokol he receives, then the notary who is responsible remains the person who made the deed. Rejection of a notary's protokol is an unlawful act, this unlawful act falls into the category of administrative violation as well as the notary's code of ethics